Modern democracy and ethical leadership in the Muslim world:A critical strategy from Tawhidic paradigm - Nabi, Ashiqun; Sarif, Suhaimi Mhd (2012)
This paper postulates critical explanation from Tawhidic paradigm on the relationship between modern democracy and ethical leadership in the Muslim world. The well established theories of democracy argued that democracy is a form of government that recognizes that all adults have equal say in the decisions that affect their lives. This paper examines how the pragmatic democracy creates ethical leadership in the governments of the Muslim world. The study conducted a survey with students from different Muslim nations to solicit their opinions on the impact of Western democracy and the creation of ethical leadership in the Muslim world. The preliminary results of the survey indicated that the Western democracy has insignificant role in creating ethical leadership from Tawhidic paradigm – the element of Unity of God. Furthermore the informants also argued that lack of accountability and transparency lead to the Muslim world to be worst off from the Modern democracy. We also came up with some strategies, how to get benefitted from this democracy in the Muslim world according to the Tawhidic Paradigm.